Predicting current and future anxiety symptoms in cognitively intact older adults with memory complaints. (3rd September 2019) - Hill, Nikki L.; Mogle, Jacqueline; Bell, Tyler Reed; Bhargava, Sakshi; Wion, Rachel K.; Bhang, Iris
Abstract : Objectives: Memory complaints are a common concern for older adults and may co‐occur with anxiety symptoms. Although both memory complaints and anxiety are associated with heightened cognitive decline risk, little is known about how these symptoms develop over time. The purpose of this study was to examine the differential concurrent and longitudinal relationships among anxiety symptoms and two types of memory complaints in cognitively intact older adults. Methods/Design: The current study sample was drawn from two longitudinal, nationally representative datasets, the National Health and Aging Trends Study (NHATS) and the Health and Retirement Study (HRS). Cognitively intact older adults aged 65 and over were included, representing six (n = 5069; NHATS) and two (n = 5284; HRS) waves of data, respectively. Using multilevel linear modeling, we tested bidirectional relationships between anxiety and two types of memory complaints: current rating of memory performance and perceived memory decline. Results: Concurrent associations between anxiety symptoms and memory complaints were found in both datasets: At times when current memory performance was rated more poorly or perceived memory decline was reported, anxiety symptoms tended to be higher, and vice versa. A longitudinal relationship was identified in NHATS such that perceived memory decline, and not current memory rating, predicted future anxiety symptoms. Conclusion: This study provides a better understanding of the relationships between memory complaints and anxiety symptoms over time. Cognitively intact older adults with perceived memory decline are at greater risk for current as well as future anxiety symptoms.